A Study of Correlation between Applied Health Literacy and Self-Care Behaviors in Hypertensive Patients of Gachsaran City, 2016 (Iran) - Mohammadtaghi Mohammadpour; Esmat Zarifinezhad; Raham Armand (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2018)
Background and Objectives: Evidences indicate that self-care in hypertension is one of the most important strategies for the control of high blood pressure. Observing self-care behaviors in patients with hypertension can help individual in regulation and control of blood pressure. One of the factors of access and awareness of health issues and, consequently, self-care is health literacy. In this study, the correlation between applied health literacy and self-care behaviors, was investigated in hypertensive patients of Gachsaran city. Methods: This study was conducted as a descriptive-analytical study on 354 patients with hypertension referring to health centers covered by Comprehensive Health Services Centers in Gachsaran county in 2016. Data were collected using demographic questionnaire, HELIA (Health Literacy for Iranian Adults) questionnaire, and Self-care Behaviors questionnaire. Results: In this study, among the 354 paticipants, the levels of health literacy were 40% adequate, 56% borderline, and 4% inadequate. There were significant correlations between the total score of health literacy and adherence to regimen diet self-care behavior (r = 0.092, p= 0.085) and physical activity as another self-care area (r = 0.122, p = 0.022) and adherence to medication regimen (r = 0.007 p = 0.038), but no significant correlation was observed between tobacco use (r = 0.010, p = 0.854) and health literacy (r = 0.1317, p = 0.35). Conclusion: The findings of the present research indicated a significant relationship between health literacy with variables of medication regimen and physical activity, and since these factors are effective in prevention and control of blood pressure, thus, measures should be taken to educate and improve health literacy in the patients under coverage.